2011 International Conference on Management and Service Science 2011
DOI: 10.1109/icmss.2011.5998239
|View full text |Cite
|
Sign up to set email alerts
|

Timely Project Completion Probability and Stability Cost on the Interaction among Uncertainty of Random Duration, Service Level and Feeding Buffer in a RCPSP Environment

Abstract: The concept of feeding buffer, proposed by Goldratt (1997), has attracted much attention to the world. There are many researches on the feeding buffer size. However, actually in real practice, even the same project may need to insert with different size of feeding buffer as different team with different level of skilled workers and different project environment with different kind of uncertainty, resulting in different kind of safety time (Newbold, 2008). In this paper, we investigate the impact of feeding buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Shi and Gong [21] took into account components such as scarcity of resources, complexity of the network and the project manager's risk profile. Zhang, Cui, Bie, and Chai [22] concluded that there is a high degree of interaction between the size of the feeding buffer, the level of service, the uncertainty of the activities duration and the whole project duration. Liu, Chen, and Peng [23] used the entropy concept to calculate the buffer size from the resource utilization factor, the network complexity and the risk aversion.…”
Section: Relevant Literature Review On Redundancy Based Methodsmentioning
confidence: 99%
“…Shi and Gong [21] took into account components such as scarcity of resources, complexity of the network and the project manager's risk profile. Zhang, Cui, Bie, and Chai [22] concluded that there is a high degree of interaction between the size of the feeding buffer, the level of service, the uncertainty of the activities duration and the whole project duration. Liu, Chen, and Peng [23] used the entropy concept to calculate the buffer size from the resource utilization factor, the network complexity and the risk aversion.…”
Section: Relevant Literature Review On Redundancy Based Methodsmentioning
confidence: 99%
“…According to the scientific literature review carried out in this research for the period 1996-2019, the solution techniques most frequently used to solve the RCPSP with random duration of activities were the Genetic Algorithms [5][6][7][8][9][10][11][12][13][14][15][16] and the Critical Chain Method [17][18][19][20][21][22][23][24][25][26][27][28]. The RCPSP with random duration of activities and stochastic tasks insertion was presented by [29].…”
Section: Resource Constrained Project Scheduling Problem With Random mentioning
confidence: 99%
“…Shi and Gong (2009) analyzed the scarce resources, network complexity and the project manager's risk profile. Zhang, Cui, Bie and Chai (2011), identified a high degree of interaction between feed buffer size, service level, uncertainty on activities duration and total project duration. Liu, Chen and Peng (2012) analyzed the resource utilization factor, the network complexity and the risk aversion.…”
Section: Cc/bm Applied To Rcpspmentioning
confidence: 99%